Pondok Boro Darmin as an Alternative Housing for Migrants in Semarang, 1980-1990 - Ahdika Ihsan Ramadhan; Bambang Rakhmanto (Tarikhuna: Journal of History and History Education, 2025)
This study examines the role of Pondok Boro Darmin as an alternative residence for migrants in Semarang during the period 1980–1990. The boarding house primarily accommodated low-income informal workers who were excluded from formal housing schemes amidst the city’s rapid urbanization. Employing a historical methodology comprising four stages—heuristics (collecting primary sources, including interviews and archival documents), source criticism (validating data), interpretation (socio-economic analysis), and historiography (historical writing)—this research situates Pondok Boro Darmin within the broader socio-economic transformations of Semarang during that era. Findings reveal that during the 1980s, accelerated economic activities in the vicinity of Pasar Johar and the city center created a demand for flexible, low-cost housing solutions for rural migrants seeking employment in trade, transportation, and informal sectors. Pondok Boro Darmin emerged as a strategic yet modest communal living space that not only provided cost-effective accommodation but also nurtured social resilience through solidarity, unwritten norms, and adaptive networks. By the close of the 1990s’ first decade, shifts in urban planning, rising land values, and increasing pressure for city modernization began to challenge the sustainability of such informal housing solutions. This temporal scope (1980–1990) thus represents a transitional period when Pondok Boro Darmin stood at the intersection of grassroots urban survival strategies and the growing tension between informal housing and formal urban development agendas